Efecto de biofertilizantes foliares en las características agronómicas de plantones de Musa sp. Clon Ingiri en vivero. Loreto, Perú. 2023 - Gomez Mendoza, Bianca Xioni (2025)
Biofertilizers are an alternative for agriculture due to its multiple aspects such as environmental, fertilizer and microorganism management. The Faculty of Agronomy presents the following research "EFFECT OF FOLIAR BIOFERTILIZERS ON THE AGRONOMIC CHARACTERISTICS OF Musa sp. CLON INGIRI SEEDLINGS IN NURSERY. LORETO, PERU. 2023", for this a Completely Randomized Block Design was used, with treatments T1 (50% Biol + 50% water), T2 (50% humus leachate + 50% water), T3 (50% worm humus leachate + 45% water + 5% EM-1) and T4 (50% Biol + 45% water + 5% EM-1). With the results, it can be said that the best results in the indicators studied were T4 (50% Biol + 45% water + 5% EM-1) and T3 (50% worm humus leachate + 45% water + 5% EM-1) and in both the effective microorganisms influence the results. In plant height, 65.88 and 64.97 centimeters were achieved with the T4 and T3 treatments. In number of plant leaves, 6.40 and 6.10 were achieved with the T4 and T3 treatments. In pseudostem diameter, 6.98 and 6.88 centimeters were achieved with the T4 and T3 treatments. In leaf length, 51.65 and 48.93 centimeters were achieved with the T4 and T3 treatments. Corm diameters were achieved with treatments T4 and T3, reaching 12.86 and 12.11 centimeters.